2018
DOI: 10.1080/15226514.2017.1337068
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced atrazine removal by hydrophyte–bacterium associations and in vitro screening of the isolates for their plant growth-promoting potential

Abstract: Emergent hydrophytes Acorus calamus, Typha latifolia, and Phragmites karka and epiphytic root bacteria isolated from their rhizoplanes were exposed to atrazine (5 and 10 mg l) individually and in plant-bacterium combination for 15 days hydroponically. It was observed that A. calamus-Pseudomonas sp. strain, the ACB combination, was best in decontamination, showing 91% and 87% removal of 5 and 10 mg l atrazine. Plant-bacterium association led to significant increase in atrazine decontamination as compared to dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The degradation rates of atrazine by the strain-wheat and strain-alfalfa systems in 30 days reached to 99.8% and 75.6%, respectively. James et al [104] isolated some Pseudomonas strains from the roots of Acorus calamus, Typha latifolia, and Phragmites karka, and employed them for the combined remediation of atrazine. It showed that the combined system of Acorus calamus and Pseudomonas strains possessed the high removal rate of atrazine, and the combination of microbes-plants could significantly improve the removal of atrazine as compared with the remediation of single plants or microorganisms.…”
Section: Plant-microbial Remediationmentioning
confidence: 99%
“…The degradation rates of atrazine by the strain-wheat and strain-alfalfa systems in 30 days reached to 99.8% and 75.6%, respectively. James et al [104] isolated some Pseudomonas strains from the roots of Acorus calamus, Typha latifolia, and Phragmites karka, and employed them for the combined remediation of atrazine. It showed that the combined system of Acorus calamus and Pseudomonas strains possessed the high removal rate of atrazine, and the combination of microbes-plants could significantly improve the removal of atrazine as compared with the remediation of single plants or microorganisms.…”
Section: Plant-microbial Remediationmentioning
confidence: 99%